Tuning the AIE Activities and Emission Wavelengths of Tetraphenylethene‐Containing Luminogens. Issue 4 (9th April 2016) - Zhou, Jian; He, Bairong; Xiang, Jiayun; Chen, Bin; Lin, Gengwei; Luo, Wenwen; Lou, Xiaoding; Chen, Shuming; Zhao, Zujin; Tang , Ben Zhong
Abstract: Aggregation‐induced emission (AIE) has attracted rapidly growing interest, owing to the high fundamental importance and diverse applications. The study of structure‐property correlation of AIE luminogens is of high importance for the design and application of new AIE luminogens. In this contribution, we synthesized two pairs of tetraphenylethene‐phenanthro[9, 10‐ d ]imidazole conjugates, and investigated the structure‐property correlation of the luminogens. The optical properties, fluorescence lifetimes, electronic structures, electrochemical properties, and electroluminescence properties of the luminogens were comparatively studied. It was found that embedding benzo‐2, 1, 3‐thiadiazole moieties into the molecular backbones not only tuned the fluorescence feature of aggregation‐enhanced emission to moderate aggregation‐caused quenching, but also strongly red‐shifted the fluorescence of luminogens from sky‐blue to red. The underlying mechanism of this phenomenon was studied and discussed combined with theoretical calculation results. Undoped organic light‐emitting diodes with varied electroluminescence colors and good performances are fabricated using these luminogens as light‐emitting layers. Abstract : Embedding the electron withdrawing benzo‐2, 1, 3‐thiadiazole into π–conjugated molecular backbone drastically red‐shifts the emission spectra and decreases the AIE activities of tetraphenylethene derivatives.